Organizações do terceiro setor envolvidas em projetos artístico-culturais : uma análise da sua gestão e da tendência dos seus gestores aos valores pós-materialistas um estudo de caso - Silva Júnior, Sinvaldo Assunção da (2011)
The present dissertation objectifies to investigate the particularities of a Third Sector organization management involved in artistic-cultural projects and the reasons of the activism of its managers, in order to search their tendency to post-materialist values, according to Inglehart. In this sense, as an important aspect of the management, it was attempted to discover in which way these managers measure the results of the actions and projects of this organization. Since this study treats with organizations involved in arts and culture, it was objectified to understand here the relation between Third Sector organizations and culture, and in which way their managers see the culture and the social contribution that were resulted from their cultural projects. In this case, the social contribution is understood as a form of result. This vision of both culture and the social contributions of culture are important in so far as they induce managers to opt for certain kinds of artistic-cultural projects, namely those using arts and culture as a medium of social transformation. Moreover, from the discussion of Inglehart s Theory of Human Development, this research objectified to verify the tendency of the managers to the materialist/post-materialist values. From the results referring to the management particularities of the studied Third Sector organization, it was concluded that, on the part of the managers, there is ignorance of some management aspects, such as finances, people management (volunteers), accountancy, marketing, and communication with the target audience. On the studied organization, the reasons of the managers activism are subjective, personal, which does not contribute for a more rational and professional vision of the attempted voluntary work. In what regards to the managers conceptions about culture, everyone see it as an instrument of social transformation, which dialogues with much of the literature about Third Sector organizations focusing in arts and culture. In this sense, the cultural actions and projects of the organization, i.e., its services/products, aim not only the target audience s entertainment, but, above all, the transmission of a greater message and, when possible, the social transformation through culture. It was also possible to verify a managers tendency to the post-materialist values, according to Inglehart.